Dynamic and elastic shape transitions in curved ESCRT-III filaments. (August 2017) - Chiaruttini, Nicolas; Roux, Aurélien
Abstract : The ESCRT-III complex is an evolutionary ancient and conserved complex that catalyzes fission of lipid membranes from the lumen of the neck in many, if not all processes requiring this specific fission reaction. The ESCRT-III membrane remodeling complex is unique as its molecular and polymeric structures do not intuitively suggests how it could deform and break lipid membranes. Here we review the common structural features of the ESCRT-III subunits, and the shape diversity of the various filamentous forms. We propose a simple geometry and elasticity framework that could help to isolate which features of the ESCRT-III filaments are common to all filamentous forms as well as to explain their diversity. We speculate on how these features could provide mechanistic insights into the many functions of the ESCRT-III complex.